Perceived Challenges in Mental Health Education Management under the Online Environment: Evidence from University Students in Guangzhou - Gui Sijie; Muhamad Sholeh; Karwanto Karwanto (MASI Mandiri Edukasi, 2026)
The online environment has reshaped how university students learn, interact, and experience psychological pressure, creating new demands for mental health education management in higher education. This study examined the perceived challenges in the management of mental health education among university students in Guangzhou in the online environment. A quantitative cross-sectional survey was conducted using a 30-item questionnaire covering six dimensions: Network Environment Impact, Screening and Early Warning, Collaborative Management, Teacher Capacity, Digital Management, and System Adaptability. Data were collected from 58 students at Guangzhou Huali College and analyzed using descriptive statistics and Cronbach’s alpha. The findings showed a moderate overall level of perceived challenge (M = 3.267, SD = 0.456). Network Environment Impact was the highest-rated dimension (M = 3.468), followed by System Adaptability (M = 3.338) and Digital Management (M = 3.328), while Teacher Capacity recorded the lowest mean (M = 3.021). The instrument demonstrated high reliability (Cronbach’s alpha = 0.919). The study indicates that student mental health education should be understood as an institutional governance issue in digitally mediated higher education and highlights the need to strengthen early warning systems, staff competence, and adaptive digital support mechanisms.